Drainage in the Aral Sea Basin: past and future - Dukhovny, Victor, author; Sokolov, Vadim, author; Ruziev, Ulugbek, author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 2000)
The geography and climate conditions definite the importance of irrigation development for life and economic activity within the Aral Sea Basin. Irrigation in Central Asia was the basis for development, employment and welfare of populations in all its history. In the conditions of arid climate the large-scale utilization of land for irrigated agriculture depends on the artificial drainage. This problem deals with two major land quality problems in the Aral Sea Basin. These are the interrelated issues of salinity and waterlogging caused by high groundwater levels. Only about 60% of the irrigated land (1999) are classified as non-saline, according to the Central Asian standards (the main criterion is total amount of toxic salts in the soil). This paper describes current situation and possible solutions for soil salinity problems in the Aral Sea Basin.
Irrigation and drainage in the new millennium
Not digitized by CSUL Digital Services.
Presented at the 2000 USCID international conference, Challenges facing irrigation and drainage in the new millennium on June 20-24 in Fort Collins, Colorado.